Pengaruh Kreativitas Guru terhadap Minat Belajar Bahasa Indonesia Siswa Kelas IV Rangang Kecamatan Pacar Kabupaten Manggari Barat - Monika Hanut; Chatarina Novianti; Benedikta Boleng (Departement of Mathematics Education, 2023)
The results of this study indicate that there is an influence of teacher creativity on students' interest in learning Indonesian in class IV Rangang, Pacar District, West Manggari Regency. This can be seen from the partial determination coefficient (R2) obtained from the calculation, namely 0.304 or 30.4%. And partly influenced by other factors, namely as much as 69.6% which is not explained in this study. (4) Based on the results of the study, it showed that the variable (X) Teacher Creativity had an effect on Interest in Learning Indonesian Language for Class IV Rangang Students, Girlfriend District, West Manggari Regency. This can be proven by the results of Simple Regression Analysis calculations to find the Effect of Teacher Creativity on Interest in Learning Indonesian for Grade IV Rangang Students, Girlfriend District, West Manggari Regency, a correlation coefficient (R) = 0.367 which states that the correlation index (r) X to Y is sufficient with an effect of 0.367 or 36.7%. This means that the correlation index (R) of the influence of teacher creativity contributes to the learning interest of Class IV Rangang students, Girlfriend District, West Manggari Regency, which is at a strong index.